Post-Pandemic COVID-19 Migration Policy: Adaptation and Resilience in Developing Countries (Case Study: Indonesian Migrant Worker Policy) - Nurtina, Sitti (The Easta Journal Law and Human Rights, 2025)
The COVID-19 pandemic has had a significant impact on international migration patterns and policies, especially in developing countries that have a high dependence on migrant workers. This study aims to examine how migration policies in developing countries such as Indonesia adapt and demonstrate resilience post-COVID-19 pandemic. This research method uses a qualitative study with a case study approach from one developing country, using a textual study method by analyzing secondary data from various related literature. The results of the study show that the pandemic has driven policy changes that are more responsive to health and economic emergencies, as well as strengthening migrant protection mechanisms. However, there are still challenges in implementing policies, especially related to cross-sector coordination and resource constraints. This study concludes that post-pandemic migration policy adaptation requires a more flexible and inclusive approach to increase the resilience of migration systems in developing countries. The implications of this study are expected to be a reference for policy makers in formulating more effective and sustainable migration strategies in the future.